Digital Marketing on the B2B Market of Construction Equipment : Doosan Infracore Europe Case - Prymak, Yana; Lhotáková, Markéta, 1971-; Nemstsveridze, Beka; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
Objective of this work is analysing an existing marketing strategy focusing on digital marketing performance and make valuable propositions of the new DOOSAN Infracore Europe digital marketing strategy, which is a top machinery manufacturer and a global leader in Infrastructure Support Business. Methodology used is survey research and case study analysis.In the first main part of the thesis the theoretical framework of the B2B Digital Marketing is presented. The theoretical part describes main differences of B2B and B2C markets and features, on which a B2B service company needs to focus on in order to develop an effective digital marketing strategy. Theory will be followed by the practical part where the theoretical framework will be applied to the practical problem examined. Second part will contain company information, its current activities in digital marketing and situation on the market. The relevant survey will be conducted and its results will be evaluated.Final part will suggest new digital marketing strategy listing specific steps to be taken in order to improve company’s digital marketing performance.
Vedoucí práce: Markéta Lhotáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses